Republic of Righteousness : the Public Christianity of the Post-Revolutionary New England Clergy, 1783-1833. - Sassi, Jonathan D. (Oxford University Press, Incorporated, 2001)
Dr Sassi examines the debate over the proper connection in society between religion and public life, that took place in the fifty years following the American Revolution.